Flood Vulnerability and Risk Assessment with Spatial Multi-criteria Evaluation - Masuya, Akiko (Springer Geography, 2013)
The objective of this chapter is to evaluate flood risk in Dhaka with geospatial techniques. Multi-temporal flood data, derived from digital elevation model and satellite imagery, were used to determine flood hazards. Census and spatial databases were used to evaluate flood vulnerability and risk zoning at a community level. The analytic hierarchy process (AHP) and weighted linear combination (WLC) methods were used to determine flood vulnerability within a geographic information system framework. The results revealed that 45 % of the study area was estimated as highly hazardous, accounting for 7 % of the total study population. Around 40 % of the communities in the study area are highly vulnerable to flood, with 8 % being extremely vulnerable. Further, more than 22 % of the population are in areas that are at high to very high risk of flood. Forty per cent of housing units are located in the high- to very high-risk zone, and around half of these were katcha houses, built using fragile construction materials—28 % of the communities in Dhaka were at high risk of flood.